1997
DOI: 10.1086/647585
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination of Healthcare Workers

Abstract: Objective:To assess factors associated with influenza vaccination of healthcare workers.Design:Cross-sectional survey.Setting:University-affiliated Veterans' Affairs medical center.Participants:Staff physicians and nurses employed by the medical center.Methods:A mailed, self-administered questionnaire.Results:The response rate was 38.0%. The mean age of the respondents was 43.6 years, 71.5% were females, and 26.2% were physicians. Nearly all of the practitioners had daily or weekly contact with elderly or high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(24 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…All studies included at least one demographic predictor (gender, age or occupation), eight studies included at least one behavioural predictor, and two studies included an organisational predictor. All studies were carried out in developed countries: six were performed in the USA,9 10 17 18 21 22 three in Europe,16 20 25 two in Canada19 23 and one in Australia,24 and one study was a multi-nationality survey 15. In most of the studies, influenza vaccines were provided for free by the hospitals on an annual, voluntary basis.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included at least one demographic predictor (gender, age or occupation), eight studies included at least one behavioural predictor, and two studies included an organisational predictor. All studies were carried out in developed countries: six were performed in the USA,9 10 17 18 21 22 three in Europe,16 20 25 two in Canada19 23 and one in Australia,24 and one study was a multi-nationality survey 15. In most of the studies, influenza vaccines were provided for free by the hospitals on an annual, voluntary basis.…”
Section: Resultsmentioning
confidence: 99%
“…We have confirmed reports from smaller studies that the uptake is poor, [3][4][5][6][7] particularly in comparison with health professionals in the USA. [8][9][10][11] However, this survey postdated a change in policy to immunise healthy NHS staff, and explored residual barriers to uptake after intensive promotion by NHS occupational health departments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of the research about reasons for accepting/refusing influenza vaccine (either seasonal or pandemic) has been undertaken amongst healthcare workers [1115] and more recently healthy adults [1618]. Studies so far have revealed that there were low levels of anxiety towards the swine flu pandemic [19, 20].…”
Section: Introductionmentioning
confidence: 99%